Cell-Specific Transcriptome Analysis Shows That Adult Pillar and Deiters' Cells Express Genes Encoding Machinery for Specializations of Cochlear Hair Cells - Liu, Huizhan; Chen, Lei; Giffen, Kimberlee P.; Stringham, Sean T.; Li, Yi; Judge, Paul D.; Beisel, Kirk W.; He, David Z. Z. (Frontiers in Molecular Neuroscience, 2018)
The mammalian auditory sensory epithelium, the organ of Corti, is composed of hair cells and supporting cells. Hair cells contain specializations in the apical, basolateral and synaptic membranes. These specializations mediate mechanotransduction, electrical and mechanical activities and synaptic transmission. Supporting cells maintain homeostasis of the ionic and chemical environment of the cochlea and contribute to the stiffness of the cochlear partition. While spontaneous proliferation and transdifferentiation of supporting cells are the source of the regenerative response to replace lost hair cells in lower vertebrates, supporting cells in adult mammals no longer retain that capability. An important first step to revealing the basic biological properties of supporting cells is to characterize their cell-type specific transcriptomes. Using RNA-seq, we examined the transcriptomes of 1,000 pillar and 1,000 Deiters’ cells, as well as the two types of hair cells, individually collected from adult CBA/J mouse cochleae using a suction pipette technique. Our goal was to determine whether pillar and Deiters’ cells, the commonly targeted cells for hair cell replacement, express the genes known for encoding machinery for hair cell specializations in the apical, basolateral, and synaptic membranes. We showed that both pillar and Deiters’ cells express these genes, with pillar cells being more similar to hair cells than Deiters’ cells. The fact that adult pillar and Deiters' cells express the genes cognate to hair cell specializations provides a strong molecular basis for targeting these cells for mammalian hair cell replacement after hair cells are lost due to damage.